2017
DOI: 10.3892/ijo.2017.3943
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic silencing of miR-130a ameliorates hemangioma by targeting tissue factor pathway inhibitor 2 through FAK/PI3K/Rac1/mdm2 signaling

Abstract: Hemangiomas are the most common vascular tumors that occur frequently in prematures and females. microRNA (miR)-130a is associated with the growth and invasion in many tumors, and its role in hemangiomas has not been addressed so far. The present study revealed that miR‑130a was overexpressed in infantile hemangioma tissues compared with matched tumor-adjacent tissues. The inhibitor of miR-130a restrained cell growth and induced cell apoptosis in vitro. miR‑130a inhibitor also induced a cell cycle arrest at G2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…Our previous data revealed the negative regulation of TFPI‐2 by promoter methylation, although this could not arbitrarily exclude the involvement of another regulatory mechanism in this setting . Therefore, we aimed to identify the potential miRs that convergently inhibited the expression of TFPI‐2 in gastric cancer.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Our previous data revealed the negative regulation of TFPI‐2 by promoter methylation, although this could not arbitrarily exclude the involvement of another regulatory mechanism in this setting . Therefore, we aimed to identify the potential miRs that convergently inhibited the expression of TFPI‐2 in gastric cancer.…”
Section: Resultsmentioning
confidence: 95%
“…suggested that miR‐616‐3p promoted cell proliferation and migration via modulating the expression of TFPI‐2 in preeclampsia. Gao et al . demonstrated that miR‐130a was subjected to epigenetic silencing in hemangioma, which consequently ameliorated the malignancy through targeting TFPI‐2 via the FAK/PI3K/Rac1/mdm2 signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐130a inhibitor represses the growth and angiogenesis of haemangioma by targeting tissue factor pathway inhibitor 2 (TFPI2) via inhibiting the focal adhesion kinase (FAK)/phosphoinositide 3‐kinase (PI3K)/Rac1/anti‐mouse double minute (mdm2) signalling pathway 108. In addition, the inhibition of miR‐130a represses cell proliferation, migration and angiogenesis in gastric cancer by enhancing runt‐related transcription factor 3 (RUNX3) protein expression 109.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
“…In addition to the lncRNAs, microRNAs (miRNAs), a subgroup of ncRNAs with about 20 nucleotides that inhibit their target gene are differentially expressed in different phase HAs [19]. Some studies showed that miR-143, miR-199a and miR-130a are involved in regulating cell proliferation and invasion in HAs cells [20][21][22]. Nevertheless, little is known about the functions and underlying mechanisms of MEG3 in the pathogenesis HAs.…”
Section: Introductionmentioning
confidence: 99%